Analysis on the Implementation of Enterprise Risk Management and the Role of Internal Audit in Business Risk Management (Case Study of PT. Bank Tabungan Negara (Persero) Tbk) - Sianturi, Fitri Leris Febriana; Zarkasyi, Wahyudin; Hasyir, Dede Abdul (Universitas Batanghari Jambi, 2025)
This study aims to analyze the implementation of Enterprise Risk Management (ERM) and the role of Internal Audit in managing business risk at PT Bank Tabungan Negara (Persero) Tbk. This study uses a qualitative approach by utilizing secondary data analysis, including annual reports, audit reports, and official publications of BTN. The focus of the study is to explore the implementation of ERM in identifying, mitigating, and controlling risks, as well as assessing the contribution of Internal Audit in ensuring compliance and providing recommendations for improvement. The results of the study indicate that the implementation of Enterprise Risk Management and the role of Internal Audit have a significant influence on business risk management at Bank BTN.